32‐1: On‐chip Red Quantum Dots in White LEDs for General Illumination. Issue 1 (30th May 2018) - Estrada, Daniel; Shimizu, Ken; Bohmer, Marcel; Gangwal, Sumit; Diederich, Thomas; Grabowski, Stefan; Tashjian, Greg; Chamberlin, Danielle; Shchekin, Oleg B.; Bhardwaj, Jyoti
Abstract : We report on white LEDs for the general illumination market with red colloidal quantum dots (QDs) applied in an on‐chip configuration. Red QDs, in combination with conventional phosphors, lead to LED conversion efficiency improvements that close the gap between 80 and 90 color rendering indexes (CRI) down to within 6% efficacy on a normalized Lm/W basis. We report on QDs colorcloud distribution compared to commercial phosphors in a large scale LED production and on a 7% performance gain from QDs in a chip on board (COB) LED device architecture.